Characters : weird and wonderful faces around us - Meyer, Hanchen (Bloemfontein: Central University of Technology, Free State, 1996)
There are people all around us, but what makes a photograph of a person or people interesting or unusual? Creativity is found in all of us, but it is up to each one to explore, to create, to capture interest and keep it. Many of the best photographers use their photographic art to interpret and comment on our world. Photography is not simply a tool of documentation. However, when a photograph is understood to be only a documentation of an object or event, the main aim is to provide a representation which is as realistic as possible. On the other hand, when a photograph is seen as an interpretation of and comment on our world, the main aim is to evoke mood and express emotion. Of course the eventual use of the photograph will influence the amount of artistic freedom one can exercise. Shooting for one's own enjoyment, the sky is the limit. Shooting for a client, there may be restrictions. The above mentioned distinction between photographs with a dominant referential function (e.g. documentary images) and photographs with a dominant expressive function (e.g. fine art photographs) serve as the point of departure for the discussion of creative people photography in this script. Discussed will be techniques for creative photography, what makes a picture creative, the lighting of portraits and how to develop an own unique style. Also added are an appendix on the tools used in graphic imaging and a short history on the apple computer since computers also play an important role in modern photography and especially in creative work since almost anything can be achieved. It is, however, up to each one to broaden their horizons.
Thesis
Keywords: Portrait photography; Characters and characteristics - Pictorial works